EFFECT OF LUMBAR STABILIZATION EXERCISE AND LUMBAR EXTENSION EXERCISE IN THE TREATMENT OF CHRONIC LOW BACK PAIN - Chitra, R. (European Scientific Journal, ESJ, 2014)
The objective of this study is to determine the effect of lumbar stabilization exercise and lumbar extension exercise in chronic low back pain patients. The study design is Randomized clinical trial. 40 patients with chronic low back pain were selected from Gee Bee Physio Clinic, Chidambaram, Cuddalore District, Tamilnadu. They were randomly divided into 2 groups. Of them, 20 patients were given lumbar stabilization exercise and the remaining 20 were given lumbar extension exercise. They both were given interferential therapy and the results were analyzed. The outcome measures used were Numerical pain rating scale for pain and the Oswestry disability questionnaire for disability. The analysis was done using two way ANOVA. The analysis of the results shows that lumbar stabilization exercise showed much improvement in both pain and disability when compared to extension exercise group.